Hox Proteins in the Regulation of Muscle Development - Poliacikova, Gabriela; Maurel-Zaffran, Corinne; Graba, Yacine; Saurin, Andrew J. (Frontiers in Cell and Developmental Biology, 2021)
Hox genes encode evolutionary conserved transcription factors that specify the anterior-posterior axis in all bilaterians. Being well known for their role in patterning ectoderm-derivatives, such as CNS and spinal cord, Hox protein function is also crucial in mesodermal patterning. While well described in the case of the vertebrate skeleton, much less is known about Hox functions in the development of different muscle types. In contrast to vertebrates however, studies in the fruit fly, Drosophila melanogaster, have provided precious insights into the requirement of Hox at multiple stages of the myogenic process. Here, we provide a comprehensive overview of Hox protein function in Drosophila and vertebrate muscle development, with a focus on the molecular mechanisms underlying target gene regulation in this process. Emphasising a tight ectoderm/mesoderm cross talk for proper locomotion, we discuss shared principles between CNS and muscle lineage specification and the emerging role of Hox in neuromuscular circuit establishment.